2018
DOI: 10.1186/s12944-018-0930-2
|View full text |Cite
|
Sign up to set email alerts
|

USF1 deficiency alleviates inflammation, enhances cholesterol efflux and prevents cholesterol accumulation in macrophages

Abstract: BackgroundThe focus of studies on high-density lipoproteins (HDL) has shifted from HDL-cholesterol (HDL-C) to HDL function. We recently demonstrated that low USF1 expression in mice and humans associates with high plasma HDL-C and low triglyceride levels, as well as protection against obesity, insulin resistance, and atherosclerosis. Here, we studied the impact of USF1 deficiency on HDL functional capacity and macrophage atherogenic functions, including inflammation, cholesterol efflux, and cholesterol accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Among the top TFs (relevance score > 0.2) that drove this trajectory, the DNA-binding RELA-NFKB1 complex is involved in several biological processes, such as inflammation, immunity, and cell growth initiated by external stimuli. MYC gene is related to the cell cycle and apoptosis pathway and upstream transcription factor 1 ( USF1 ) is related to metabolic alteration associated inflammation process (Ruuth et al 2018 ). In summary, the TF results are well consistent with our previous hallmark pathway findings (Supplementary Table S5 and S6).…”
Section: Resultsmentioning
confidence: 99%
“…Among the top TFs (relevance score > 0.2) that drove this trajectory, the DNA-binding RELA-NFKB1 complex is involved in several biological processes, such as inflammation, immunity, and cell growth initiated by external stimuli. MYC gene is related to the cell cycle and apoptosis pathway and upstream transcription factor 1 ( USF1 ) is related to metabolic alteration associated inflammation process (Ruuth et al 2018 ). In summary, the TF results are well consistent with our previous hallmark pathway findings (Supplementary Table S5 and S6).…”
Section: Resultsmentioning
confidence: 99%
“…USF1 is a transcription factor that modulates several genes involved in lipid and glucose metabolism such as apolipoproteins and lipases including PNPLA2, a triglyceride lipase that catalyzes the initial step in triglyceride hydrolysis (Aguilar-Salinas et al, 2014;Taghizadeh et al, 2019). Knockout studies of USF1 in mice have been shown to enhance cholesterol efflux in macrophages and downregulate secretion of pro-inflammatory cytokines such as MCP-1 and IL-1b (Ruuth et al, 2018) and USF1 variants in humans have been associated with familial combined hyperlipidemia and coronary artery disease (Fan et al, 2014;Laurila et al, 2016;Ruuth et al, 2018). Interestingly, a recent study by Dias et al showed that monocytes from COVID-19 have increased lipid droplet accumulation and that pharmacological inhibition of lipid droplet formation led to a significant inhibition of replication of SARS-CoV-2 (Dias et al, 2020).…”
Section: Ll Open Access Isciencementioning
confidence: 99%
“…Since macrophages as scavenging cells cannot limit the intake of cholesterol-rich lipoprotein particles, they rely fully on active transport of cholesterol out of the cell via ATP-binding cassette transporters such as ABCA1 and ABCG1 to overcome their transformation into foam cells 21 . In vitro studies have recently shown that elimination of USF1 from human THP-1 macrophages induces cellular ABCA1 protein levels and a parallel rise in the rate of cholesterol efflux to wild-type mouse serum 18 . Furthermore USF1 deficient macrophages displayed reduced inflammatory burden with reduced secretion of the pro-inflammatory cytokines monocyte chemoattractant protein-1 and interleukin-1β, thereby supporting the cholesterol efflux process 18 .…”
Section: Introductionmentioning
confidence: 99%